2008
DOI: 10.3892/or.19.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of fermented brown rice and rice bran on N-methyl-N'-nitro-N-nitrosoguanidine-induced gastric carcinogenesis in rats

Abstract: A number of possible preventive agents for cancers in different organs have been reported, however, little information is available regarding the effective agents for the development of gastric cancers. The rice components are known to be effective for the prevention of the development of cancers. Our group has demonstrated that fermented brown rice by Aspergillus Orzae (FBRA) has chemopreventive potentials in several organs. In this study, we investigated the modifying effects of FBRA exposed during the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
(30 reference statements)
2
30
1
Order By: Relevance
“…A number of studies have shown the chemopreventive effect of fermented brown rice and rice bran (FBRA) on several types of cancer, including colon cancer (12)(13)(14)(15). In contrast to previous findings that FBRA significantly suppressed azoxymethane-induced colorectal carcinogenesis in rats, in the present study, FBRA has no effect on the tumor development of the colon in Apc Min/+ genetic background.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…A number of studies have shown the chemopreventive effect of fermented brown rice and rice bran (FBRA) on several types of cancer, including colon cancer (12)(13)(14)(15). In contrast to previous findings that FBRA significantly suppressed azoxymethane-induced colorectal carcinogenesis in rats, in the present study, FBRA has no effect on the tumor development of the colon in Apc Min/+ genetic background.…”
Section: Discussioncontrasting
confidence: 55%
“…Fermented brown rice and rice bran (FBRA) is a processed food prepared by fermented the brown rice and rice bran with Aspergillus oryzae. In our previous studies, FBRA showed chemopreventive effect against various types of chemically-induced cancer, including colon (12), stomach (13), bladder (14) and esophagus (15) …”
Section: Introductionmentioning
confidence: 99%
“…Groups II and III: treated with 0.1g/L of MNNG with distilled water prepared thrice per week for 24 weeks according to the protocol described in previous reports (Hu et al, 2004;Okazaki et al, 2006;Tomita et al, 2008). The MNNG solution was protected from light and given ad libitum to rats through drinking water.…”
Section: Methodsmentioning
confidence: 99%
“…BRA has attracted attention as a macrobiotic functional food with possible physiological activity. BRA is an effective chemo preventive agent against inflammation-related gastric [13] and colorectal [14] carcinogenesis, and reduces expression of inflammation-related genes, such as TNF-α, Mac-1, CCL 3, and CXCL 2 [15]. Changes in nutrition during food processing can directly affect the food function, though this has not been sufficiently examined.…”
Section: Introductionmentioning
confidence: 99%